Fluorescence Imaging of Head and Neck Squamous Cell Carcinoma. (2nd September 2014) - Hauff, Samantha J.; Raju, Sharat C.; Orosco, Ryan K.; Nashi, Nadia; Savariar, Elamprakash N.; Tsien, Roger Y.; Nguyen, Quyen T.
Abstract : Objectives: (1) Demonstrate that head and neck squamous cell carcinoma (HNSCC) can be fluorescently imaged using a matrix metalloproteinase (MMP)‐cleavable, ratiometric activatable cell‐penetrating peptide (RACPP). (2) Correlate extent of tumor involvement with fluorescent signal. Methods: Increased expression of MMP‐2 and MMP‐9 has been well documented in multiple cancers. We developed an injectable probe (RACPP) that exhibits ratiometric fluorescence (increased Cy5:Cy7 ratio) when cleaved by these proteinases. To examine the utility of MMP2, 9‐cleavable RACPPs in HNSCC, mice were injected with 5 human HNSCC cell lines to establish orthotopic tongue xenografts (n = 22). Tumor‐bearing mice were imaged in‐vivo after intravenous RACPP injection. Fluorescent signal was correlated with histology by a blinded pathologist. Gelatinase zymography confirmed MMP‐2, 9 activity in these xenografts. For ex‐vivo analysis of human HNSCC specimens, RACPP was applied to homogenized samples (n = 5), and fluorescence was measured on a microplate reader. Results: Orthotopic tongue HNSCC xenografts showed excellent ratiometric fluorescent labeling with MMP2, 9‐cleavable RACPP (sensitivity = 95.4%, specificity = 95.0%). Signal intensity, as defined by ratiometric contrast, was greater in areas of higher tumor burden ( P <. 03). Ex vivo human HNSCC specimens treated with MMP2, 9‐cleavable RACPP also had increased signal intensity when compared to normal human fat ( P =. 005). Conclusions: Fluorescent labeling with MMP2, 9‐cleavable RACPP is an effective way to visualize HNSCC in‐vivo in a murine model, and signal intensity correlates with tumor burden. RACPPs have the potential to improve occult tumor identification and margin clearance in HNSCC. Ex‐vivo assays using biopsy specimens may help identify patients who will benefit from intraoperative RACPP use and may be useful in retrospective analyses.